Pengembangan Modul Pembelajaran â€œDianaâ€ (Media Baca Anak) untuk Anak Cerebral Palsy - Assabilia, Nadhila Berlian; Iftayani, Itsna; Kusumastuti, Wanodya (Universitas PGRI Semarang, 2024)
This developmental research aims to improve the reading ability of children with cerebral palsy. The study resulted in a learning module product called